«The fifth generation» of heads of the People’s Republic of China. - Arzykulov., A. A. (Journal of Oriental Studies, 2016)
In this article the XVIII congress of a Communist party of China and coming to power of «the fifth generation» of the Chinese heads is considered. Many complex challenges face the new management and from the solution of these problems the future of the country can depend. First stage, of course achievements of «the Chinese dream».